2011
DOI: 10.1590/s0034-89102011005000070
|View full text |Cite
|
Sign up to set email alerts
|

Anos potenciais de vida perdidos e custos hospitalares da leptospirose no Brasil

Abstract: There was a high social cost in terms of years of potential life lost and partial hospital costs associated with leptospirosis when compared to the possibility of early treatment or prevention of infection, both of which could minimize the impact of the disease on the Brazilian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
22

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 15 publications
3
28
0
22
Order By: Relevance
“…Souza et al [36] estimated the costs of hospitalization and years of potential life lost associated with leptospirosis in Brazil in 2007. The study found that 331 patients died, corresponding to an average of 30 years of potential life lost for each death.…”
Section: Resultsmentioning
confidence: 99%
“…Souza et al [36] estimated the costs of hospitalization and years of potential life lost associated with leptospirosis in Brazil in 2007. The study found that 331 patients died, corresponding to an average of 30 years of potential life lost for each death.…”
Section: Resultsmentioning
confidence: 99%
“…Sobre os artigos analisados, ao longo do período proposto, observa-se uma tendência crescente até o ano de 2011, e este mesmo ano culmina com a maior quantidade de publicações (2011 [16][17][18][19] 35,36 .…”
Section: Resultsunclassified
“…(20) The phase of the epidemiological investigation of dengue cases is a very important step to detect the likely site of infection, to break the chain of transmission, and to prevent outbreaks. (14,21) In the analysis of the research timeliness, an excellent performance of the surveillance system was observed -between 90% and 96% of cases initiated investigations on the day of notification. Similar results were found in the evaluation of the national dengue system at 90%, (15) and in the study of the national databank of leptospirosis at 89%.…”
Section: Discussionmentioning
confidence: 97%